Some Functional Equations and Their Corresponding Sum Forms - Nath, Prem; Singh, Dhiraj Kumar (Sarajevo Journal of Mathematics, 2024)
The general solutions of some functional equations containing at least two unknown mappings have been obtained without imposing any regularity condition on any of the mappings.